Pleasurable and Intersubjectively Embodied Experiences of Electronic Dance Music - Solberg, Ragnhild Torvanger; Jensenius, Alexander Refsum (Empirical Musicology Review, 2017)
How do dancers engage with electronic dance music (EDM) when dancing? This paper reports on an empirical study of dancers' pleasurable engagement with three structural properties of EDM: (1) breakdown, (2) build-up, and (3) drop. Sixteen participants danced to a DJ mix in a club-like environment, and the group’s bodily activity was recorded with an infrared, marker-based motion capture system. After they danced, the subjects filled out questionnaires about the pleasure they experienced and their relative desire to move while dancing. Subsequent analyses revealed associations between the group’s quantity of motion and self-reported experiences of pleasure. Associations were also found between certain sonic features and dynamic changes in the dancers' movements. Pronounced changes occurred in the group's quantity of motion during the breakdown, build-up, and drop sections, suggesting a high level of synchronization between the group and the structural properties of the music. The questionnaire confirmed this intersubjective agreement: participants perceived the musical passages consistently and marked the build-up and drop as particularly pleasurable and motivational in terms of dancing. Self-reports demonstrated that the presence and activity of other participants were also important in the shaping of one's own experience, thus supporting the idea of clubbing as an intersubjectively embodied experience.